Development of Efficient Algorithms for the Computation of Complex Integrals Based on Mathematical Theorems - Yuldasheva Shakhlo Otabekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The computation of complex integrals is widely applied in mathematical analysis, as well as in physics, engineering, and computer science. This article analyzes the main theorems used in the evaluation of complex integrals and efficient computational algorithms implemented in the Python programming language. The practical application of these theorems, along with numerical and graphical methods for evaluating integrals, is also presented.